2023
DOI: 10.1248/cpb.c23-00518
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical Food Science: Search for Bio-Functional Molecules Obtained from Natural Resources to Prevent and Ameliorate Lifestyle Diseases

Toshio Morikawa

Abstract: In this review, our resent pharmaceutical food science research for bio-functional molecules obtained from natural resources that contribute to i) suppression of postprandial blood glucose elevation and/or improvement of glucose tolerance and ii) reduction of visceral fat accumulation and improvement of lipid metabolism were summarized. Based on studies using MONOTORI science, salacinol (1), neokotalanol (4), and trans-tiliroside (20) have been approved or notified by the Consumer Affairs Agency in Japan as fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 118 publications
0
1
0
Order By: Relevance
“…1 ) contained in rose hip seeds has been reported to exhibit various pharmacological activities, including anti-inflammatory [ 15 ], antioxidant [ 16 ], anticancer [ 17 , 18 ], tyrosinase inhibitory [ 19 ], and hepatoprotective [ 20 ] effects. We have previously reported that compound 1 potently suppresses body weight gain in mice [ 21 , 22 ], increases mRNA expression of peroxisome proliferator-activated receptor α [ 21 ], which regulates lipid metabolism, and reduces intracellular TG and enhances glucose metabolism in human hepatocellular carcinoma-derived HepG2 cells [ 22 , 23 ]. Studies on lipid metabolism of compound 1 have focused on the decrease in TG in the liver and muscle [ 21 , 24 ], with few studies on CHO having been conducted.…”
Section: Introductionmentioning
confidence: 99%
“…1 ) contained in rose hip seeds has been reported to exhibit various pharmacological activities, including anti-inflammatory [ 15 ], antioxidant [ 16 ], anticancer [ 17 , 18 ], tyrosinase inhibitory [ 19 ], and hepatoprotective [ 20 ] effects. We have previously reported that compound 1 potently suppresses body weight gain in mice [ 21 , 22 ], increases mRNA expression of peroxisome proliferator-activated receptor α [ 21 ], which regulates lipid metabolism, and reduces intracellular TG and enhances glucose metabolism in human hepatocellular carcinoma-derived HepG2 cells [ 22 , 23 ]. Studies on lipid metabolism of compound 1 have focused on the decrease in TG in the liver and muscle [ 21 , 24 ], with few studies on CHO having been conducted.…”
Section: Introductionmentioning
confidence: 99%